2003
DOI: 10.1016/s1063-4584(03)00150-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of reactive oxygen species in homeostasis and degradation of cartilage

Abstract: This review of the literature supports the concept that ROS are not only deleterious agents involved in cartilage degradation, but that they also act as integral factors of intracellular signaling mechanisms. Further investigation is required to support the concept of antioxidant therapy in the management of joint diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
495
1
20

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 660 publications
(525 citation statements)
references
References 70 publications
9
495
1
20
Order By: Relevance
“…This result could provide evidence of an increased extracellular matrix protein nitration in equine osteochondral lesions, since until recently, nitrotyrosine (NO (2) Tyr) formation has been considered to be a specific marker for protein oxidation by peroxynitrite (ONOO -), an unstable oxidant formed during neardiffusion limited interaction of superoxide ( ) and nitric oxide ) (Baldus et al, 2002;Brennan et al, 2002). Superoxide anion and nitric oxide productions in chondrocyte and in synovial cultures have been widely demonstrated (Stichtenoth and Frölich, 1998;Henrotin et al, 2003). However, in recent years other pathways of nitrotyrosine-formation have been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…This result could provide evidence of an increased extracellular matrix protein nitration in equine osteochondral lesions, since until recently, nitrotyrosine (NO (2) Tyr) formation has been considered to be a specific marker for protein oxidation by peroxynitrite (ONOO -), an unstable oxidant formed during neardiffusion limited interaction of superoxide ( ) and nitric oxide ) (Baldus et al, 2002;Brennan et al, 2002). Superoxide anion and nitric oxide productions in chondrocyte and in synovial cultures have been widely demonstrated (Stichtenoth and Frölich, 1998;Henrotin et al, 2003). However, in recent years other pathways of nitrotyrosine-formation have been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…In these conditions, high levels of pro-inflammatory cytokines such as interleukin(IL)-1have been found in synovial fluids and may participate in collagen and proteoglycan degradation [1,2]. Moreover, chondrocyte activation by proinflammatory cytokines has been implicated in joint destruction through the production of catabolic enzymes and inflammatory mediators such as reactive oxygen species (ROS) and prostaglandin E 2 (PGE 2 ) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…ROS can modulate cell signaling and exert damaging effects on cartilage as a consecuence of extracellular matrix degradation or chondrocyte apoptosis [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports also revealed that chondrocyte aging is closely involved in oxidative stress, such as the induction of ROS by extrinsic stress (e.g., mechanical force) in degenerated articular cartilage (11)(12)(13)19,23). It has been reported that oxygen-derived free radicals directly damage the guanine repeats in the telomere DNA (24)(25)(26)(27).…”
mentioning
confidence: 99%